Waste management without direction in Indonesia: a proposed legal reform towards smart cities - Listiningrum, Prischa; Dahlan, Moh.; Anwary, Muhammad Anis Zhafran Al; Wahyuni, Herlin Sri; Bachtiar, Rizqi (Legality : Jurnal Ilmiah Hukum, 2023)
This article delves into the regulation of municipal solid waste management (MSW) in Indonesia, viewed from the concepts of smart city and circular economy. The legal politics of Law Number 18 of 2008 on Waste Management has been restricted to the concept of 3Rs: reduce, reuse, and recycle. The idea of a circular economy refers to the principle of 10 Rs, consisting of refuse, rethink, reduce, reuse, repair, refurbish, remanufacture, repurpose, recycle, and recover. The concept of circular economy is believed to be essential to achieving the decarbonization goals mandated by the Paris Agreement. With a socio-legal approach, this research examines to what extent Waste Management Law can serve as the basis for implementing a circular economy in municipal areas. This research reveals that the concept of a circular economy has yet to be applied to manage waste in a municipal scope. Circular economy-based smart cities in MSW management can only be achieved through adequate facilities and changes in people’s behaviour. However, it is still questionable whether the Municipal Government is fully obliged to manage household waste because the Waste Management Law is silent on this matter but clearly states the community’s obligation to reduce and handle household waste as a waste producer. The division of waste-handling tasks also exacerbates this in several agencies, which, in practice, creates confusion for society. Hence, legal reforms are needed to reconcile the conflicting problems.